Experimental characterisation of the weld pool expansion in a tungsten inert gas configuration. (19th May 2017) - Stadler, M.; Masquère, M.; Freton, P.; Gonzalez, J.-J.
ABSTRACT: In this study, we focus on the expansion of the weld pool in a welding process by tungsten inert gas (TIG). Use of high-speed imaging and metallographic investigations combined with electrical measurements allow us to determine the weld pool shape and dimensions evolution and the energy involved in the process for six durations of interaction (from 1 to 20 s) in a spot TIG configuration. Results show a fast increase of the weld dimensions on the first second. Otherwise, time does not seem to be an influent parameter on the weld shape. The comparison between experimental work and numerical model available in our team highlights differences between the predicted shapes and the observed ones.